An Energy Potential Estimation of Rice Residue in Indonesia: A Case Study in East Java. Issue 1 (1st May 2022) - Rhofita, E I; Rachmat, R; Mayer, M; Montastruc, L
Abstract: East Java is one of Indonesia's largest provinces, where rice production always rises every year. The average rice yield from 2008 to 2018 was 247, 014.32 tonnes. It will produce a significant quality of biomass, which may be used to generate bioenergy. This study contributes to assessing the energy potential of rice residues such as rice straw and rice husk. It refers to the estimated energy potential of post-harvest residue in 29 districts and 9 cities, based on annual statistical data of rice production and integrated into a geospatial retrieval. The result indicates that rice straw and rice husk's development potential has significantly increased around 8% during the last decade. In 2018, the 38 East Java areas had a combined rice straw and rice husk potential of around 415, 970.61 and 55, 462.75 tonnes, respectively, equivalent to 238, 526 TJ and 32, 752 TJ of electrical power potential of around 66 GWh and 9 GWh. Over 20 locations had over 1 TWh of potential power energy of rice straw in all years, although the potential power energy of rice husk occurred since 2011. Overall, utilizing rice residue in small communities would reduce environmental issues and dependency on fossil fuels.